Simulation of Digital Radio Mondiale (DRM) Coverage Prediction – A study case with Radio Republik Indonesia (RRI) - Nabila Husna Shabrina (Universitas Multimedia Nusantara, 2017)
In this paper, DRM is applied for simulating coverage prediction in Radio Republik Indonesia (RRI). The proposed method is developed by simulating high frequency propagation from RRI Pro 3 transmitter with VOACAP online software. The simulation is undertaken in some different conditions. The variation of antenna type and transmitter power are observed in the simulation. The time of propagation also discussed to predict the coverage. The result shows that the variation of parameter influences the coverage result of DRM propagation in HF band. Changing the antenna type and time of propagation will make impact in the range of coverage while adding power transmitter gives insignificantly effect to the range of coverage. Keywords—DRM, Prediction Coverage, VOACAP REFERENCES [1] ITU R-REP-BS.2144-2009-PDF-E, “Planning parameters and coverage for Digital Radio Mondiale (DRM) broadcasting at frequencies below 30 MHz”, 2009. [2] M. J. Bradley, “Digital Radio Mondiale: System and Receivers”,Roke Manor Research Ltd, UK, 2003 [3] G. Prieto, I. Pichel, D. Guerra, P. Angueira, J.M. Matias, J.L. Ordiales, A. Arrinda, “Digital Radio Mondiale: Broadcasting and Reception”, IEEE Press, 2004. [4] DRM Features, available under http://www.drm.org [5] “Digital Radio Mondiale (DRM); System Specification,” European Telecommunication Standards Institute (ETSI), ETSI TS 101980, 2001. [6] D. Setiawan, “Alokasi Frekuensi, Kebijakan dan Perencanaan Spektrum Indonesia”, Departemen Komunikasi dan Informatika, 2010. [7] P.A Bradley, Th Dambold, P.Suessmann, “Propagation model for HF Radio Service Planning”, HF Radio Systems and Techniques, Conference Publication No 474 0 IEE, 2000. [8] J.J. Carr, “Practical Antenna Handbook 4th Edition”, McGraw Hill, 1990. [9] J.M Matias et al, “DRM (Digital Radio Mondiale) Local Coverage Tests Using the 26 Mhz Broadcasting Band”, IEEE Transactions on Broadcasting, Vol. 53, No. 1, August 2007. [10] C. A. Balanis, “Antenna Theory Analysis and Design”, 2nd ed, John Wiley & Sons, 2005. [11] Keputusan Direktorat Jendral Pos dan Telekomunikasi Nomor 85/DIRJEN/1999, “Spesifikasi Teknis Perangkat Telekomunikasi, Persyaratan Teknis Perangkat Radio Siaran”, Jakarta, 1999.